Ferroelectricity and negative piezoelectric coefficient in orthorhombic phase pure ZrO2 thin films. (February 2023) - Silva, José P.B.; Istrate, Marian C.; Hellenbrand, Markus; Jan, Atif; Becker, Maximilian T.; Symonowicz, Joanna; Figueiras, Fábio G.; Lenzi, Veniero; Hill, Megan O.; Ghica, Corneliu; Romanyuk, Konstantin N.; Gomes, Maria J.M.; et al.
Highlights: Ferroelectric orthorhombic phase pure ZrO2 thin films achieved through substrate orientation control. ZrO2 films grown epitaxially directly on Nb:STO (011) single crystal substrates via domain matching epitaxial growth. Orthorhombic phase pure ZrO2 films with spontaneous polarization of ∼14 µC/cm 2 and coercive field of ∼1.4 MV/cm. Unprecedented negative piezoelectric coefficient in the ZrO2 films. Abstract: A new approach for epitaxial stabilisation of ferroelectric orthorhombic ( o -) ZrO2 films with negative piezoelectric coefficient in ∼ 8nm thick films grown by ion-beam sputtering is demonstrated. Films on (011)-Nb:SrTiO3 gave the oriented o -phase, as confirmed by transmission electron microscopy and electron backscatter diffraction mapping, grazing incidence x-ray diffraction and Raman spectroscopy. Scanning probe microscopy techniques and macroscopic polarization-electric field hysteresis loops show ferroelectric behavior, with saturation polarization of ∼14.3 µC/cm 2, remnant polarization of ∼9.3 µC/cm 2 and coercive field ∼1.2 MV/cm. In contrast to the o- films grown on (011)-Nb:SrTiO3, films grown on (001)-Nb:SrTiO3 showed mixed monoclinic ( m -) and o -phases causing an inferior remnant polarization of ∼4.8 µC/cm 2, over 50% lower than the one observed for the film grown on (011)-Nb:SrTiO3 . Density functional theory (DFT) calculations of the SrTiO3 /ZrO2 interfaces support the experimental findings of a stable polar o- phase for growth on (011) Nb:SrTiO3, and they also explain the negative piezoelectric coefficient. Graphical abstract: Image, graphical abstract